Elasticity of Demand for Foods in Bulgaria - Ignatova, Nikolinka (Research Papers, 2023)
The present study examines the elasticity of demand for foods in Bulgaria. The latter includes – vegetables, fruits, sausages, dairy products, alcoholic beverages, non-alcoholic beverages, bread, etc. An assessment of the macro-environmental factors that impact the demand for foods in 2020 – 2021 has been made. Calculated are the price and the income elasticity of the demand for such goods. Quantified is their influence on food sales for the sub-period 2021 – July 2022. The research employs a comparative method of analysis and a historical approach. The information used is from the NSI, the statistical Yearbook and Infostat.
Keywords: Foods; Coefficient of elasticity; Income; Price; Sales